The Microbiome and Alzheimer’s Disease: Potential and Limitations of Prebiotic, Synbiotic, and Probiotic Formulations - Arora, Karan; Green, Miranda; Prakash, Satya (Frontiers in Bioengineering and Biotechnology, 2020)
The Microbiome has generated significant attention for its impacts not only on gastrointestinal health, but also on signaling pathways of the enteric and central nervous system via the microbiome gut–brain axis. In light of this, microbiome modulation may be an effective therapeutic strategy for treating or mitigating many somatic and neural pathologies, including neurodegenerative disorders. Alzheimer’s disease (AD) is a chronic neurodegenerative disease that interferes with cerebral function by progressively impairing memory, thinking and learning through the continuous depletion of neurons. Although its etiopathogenesis remains uncertain, recent literature endorses the hypothesis that probiotic, prebiotic and synbiotic supplementation alters AD-like symptoms and improves many of its associated disease biomarkers. Alternatively, a dysfunctional microbiota impairs the gut epithelial barrier by inducing chronic gastric inflammation, culminating in neuroinflammation and accelerating AD progression. The findings in this review suggest that probiotics, prebiotics or synbiotics have potential as novel biological prophylactics in treatment of AD, due to their anti-inflammatory and antioxidant properties, their ability to improve cognition and metabolic activity, as well as their capacity of producing essential metabolites for gut and brain barrier permeability.